2022
DOI: 10.31223/x5tg8q
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A record of plume-induced plate rotation triggering seafloor spreading and subduction initiation

Abstract: The formation of a global network of plate boundaries surrounding a mosaic of lithospheric fragments was a key step in the emergence of Earth’s plate tectonics. So far, propositions for plate boundary formation are regional in nature but how plate boundaries are being created over 1000s of km in short periods of geological time remains elusive. Here, we show from geological observations that a >12,000 km long plate boundary formed between the Indian and African plates around 105 Ma with subduction segments … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…We test our concept of a plate tectonic chain reaction through a case study of the initiation of a major intra-oceanic subduction zone in the Neotethys Ocean. During the mid-Cretaceous, an intra-oceanic subduction zone formed from a trench-trench-trench triple junction with a subduction zone that had already existed since Jurassic time along the southern Eurasian margin 19,22 to the west Indian Ocean, where the plate boundary transitioned into a rift (and later ridge) that ended in a ridge-ridge-ridge triple junction in the Southern Ocean 11 . This initiation of the intra-Neotethyan subduction zone generated a socalled double, in-line subduction zone configuration between Africa and Eurasia and formed a new plate consisting predominantly of Neotethyan oceanic lithosphere 23 (Fig.…”
Section: Intra-neotethyan Subduction Initiation: Start Of a Tectonic Chain Reaction?mentioning
confidence: 99%
See 4 more Smart Citations
“…We test our concept of a plate tectonic chain reaction through a case study of the initiation of a major intra-oceanic subduction zone in the Neotethys Ocean. During the mid-Cretaceous, an intra-oceanic subduction zone formed from a trench-trench-trench triple junction with a subduction zone that had already existed since Jurassic time along the southern Eurasian margin 19,22 to the west Indian Ocean, where the plate boundary transitioned into a rift (and later ridge) that ended in a ridge-ridge-ridge triple junction in the Southern Ocean 11 . This initiation of the intra-Neotethyan subduction zone generated a socalled double, in-line subduction zone configuration between Africa and Eurasia and formed a new plate consisting predominantly of Neotethyan oceanic lithosphere 23 (Fig.…”
Section: Intra-neotethyan Subduction Initiation: Start Of a Tectonic Chain Reaction?mentioning
confidence: 99%
“…But to set off a global plate reorganization, plate motion changes induced by such isolated dynamic triggers must be able to cascade to neighbouring plates, for which a mechanism has so far not been identified.We hypothesize that when a trigger causes a plate motion change, this change may in turn trigger subsequent plate motion changes, in what we conceptualize as a 'plate tectonic chain reaction'.Geodynamic analysis has long identified that the main drivers of plate motion are the negative buoyancy of subducted lithosphere (slab pull), and occasional short-lived and subtle effects of spreading mantle plume heads below the lithosphere (plume push [9][10][11] ). Formation of new, or the abandonment of preexisting plate boundaries (mid-oceanic ridges or subduction zones), at times combined with the arrival of mantle plumes, are thus widely regarded to form the dynamic underpinning of observed plate motion changes 7,[9][10][11][12][13][14][15] . Initiation of subduction of a plate, either spontaneously 16 or forced (for instance by ridge subduction 7,17 , or by arrest, relocation, or reversal of subduction) will change where and on which plates slab pull is exerted 14 .…”
mentioning
confidence: 99%
See 3 more Smart Citations